Западные культурно-экономические связи населения Юго-Западной Украины в финальном палеолите и мезолите - Киосак, Д.В. (Материалы по археологии Северного Причерноморья, 2010)
The paper treats the issues of cultural and economic relationship of the Final Palaeolithic and Mesolithic population of South-Western Ukraine. The author argues that trapezoids of Mediterranean Final Palaeolithic are not good analogies for elongated trapezes of Tsarynka and the parallels should be searched in the Central European cultural entities. The sites of Bilolissja type are related to the Cuina Turcului sites and the Recent Mesolithic finds close parallels into Pontic Tardenoisian of Romania.